Prevalence and Risk Factors of Keratoconus in Iran: A Narrative Review - Nassiri, Nader; Shahriari , Mansoor; Kavousnezhad , Sara; Yadgari, Maryam (Journal of Ophthalmic and Optometric Sciences, 2024)
Purpose: Keratoconus (KCN) is a progressive ectatic disorder of the cornea with variable prevalence across populations. This narrative review synthesizes evidence on the prevalence and risk factors of KCN in Iran, highlighting regional and genetic heterogeneity. Materials and Methods: A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, SID, and MagIran for studies published between 1990 and 2025. Eligible studies included population-based surveys and case-control analyses reporting on KCN prevalence and risk factors in Iranian populations. Results: Prevalence estimates in Iran range from 0.76 % in Shahroud to 4.0 % in rural regions, with localized values reaching 3.3 % in Tehran. Significant geographic and ethnic variation was observed, including higher prevalence among non-Persian ethnic groups. Major risk factors include family history, consanguinity, eye rubbing, vernal keratoconjunctivitis, and low socioeconomic status. Genetic studies identified associations with polymorphisms in COL4A4, TIMP-1, KIF26B, and LOX, while VSX1 and MIR184 showed no pathogenic involvement. Environmental factors such as ultraviolet radiation, arid climate, and low humidity also contribute. Behavioral and inflammatory mechanisms, particularly eye rubbing and allergic symptoms were consistently linked to disease onset and progression. Conclusion: KCN in Iran exhibits substantial regional, ethnic, and genetic diversity. Gene–environment interactions appear central to disease risk. National-level surveillance, standardized diagnostics, and multicenter genetic studies are needed to improve early detection and guide tailored interventions. The scarcity of available studies underscores the urgent need for expanded epidemiological and genetic research to address regional disparities and refine preventive strategies.